1987
DOI: 10.1111/j.1600-0714.1987.tb00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokeratins in odontogenic jaw cysts: monoclonal antibodies reveal distinct variation between different cyst types

Abstract: Immunostaining with monoclonal antibodies was used to study and compare the cytokeratin content of odontogenic cysts and normal gingival epithelium. Two monoclonal antibodies, PKK2 and KA1, stained the whole epithelium in all cyst samples. In gingivu, PKK2 gave a suprabasal staining and KA1 reacted with all epithelial cell layers. Antibodies PKK1, KM 4.62 and Ks 8.12 gave a heterogeneous staining in follicular and radicular cysts. In keratocysts and in gingiva PKK1 and KM 4.62 reacted mainly with basal cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 19 publications
8
45
0
2
Order By: Relevance
“…Odontogenic keratocysts show a particular tendency to recur after their surgical removal that could be due to a multilocular nature or a presence of daughter or satellite cysts that are left behind. However, it has also been hypothesized that the epithelium of these cysts could have an intrinsic potential to growth, resembling benign neoplasms (7). Ameloblastomas are tumors that arise from rests of the dental lamina.…”
Section: Discussionmentioning
confidence: 99%
“…Odontogenic keratocysts show a particular tendency to recur after their surgical removal that could be due to a multilocular nature or a presence of daughter or satellite cysts that are left behind. However, it has also been hypothesized that the epithelium of these cysts could have an intrinsic potential to growth, resembling benign neoplasms (7). Ameloblastomas are tumors that arise from rests of the dental lamina.…”
Section: Discussionmentioning
confidence: 99%
“…In other research studies using monoclonal antibodies LH2 and LH3, CK 10 was not observed in OKCs 18 . In 1987, Hormia et al 19 reported that CK 10 was not observed in OKCs but was observed in 2 out of 18 cases of dentigerous cysts because a different type of antibody was used for cytokeratin. Note, however, that some research studies showed different results even when the same antibody (LH3, LH2) was used for CK 10 in the epithelial tissue of OKCs [18][19][20]28 .…”
Section: Methodsmentioning
confidence: 99%
“…In 1987, Hormia et al 19 reported that CK 10 was not observed in OKCs but was observed in 2 out of 18 cases of dentigerous cysts because a different type of antibody was used for cytokeratin. Note, however, that some research studies showed different results even when the same antibody (LH3, LH2) was used for CK 10 in the epithelial tissue of OKCs [18][19][20]28 . In this research, CK 10 was observed in the suprabasal layer, with much higher frequency and intensity of expression in OKCs than dentigerous cysts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Odontogenickeratocysts show a particular tendency to recur after their surgical removal that could be due to a multilocular nature or a DOI: http://dx.doi.org/10.22192/ijcrcps.2016.03.09.008 presence of daughter or satellite cysts that are left behind. However, it has also been hypothesized that the epithelium of these cysts could have an intrinsic potential to growth, resembling benign neoplasms (2). Amelobelastomas are tumors that arise from rests of the dental lamina.…”
Section: Introductionmentioning
confidence: 99%